Impact of Leverage, Capital Intensity, Inventory Intensity, Cash Effective Tax Rate on Tax Avoidance: Assessment for Energy Sector Corporate - Donny Maha Putra; Andrea Putri Kirana (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study looks at how the Cash Effective Tax Rate (CETR) explicitly evaluates the effects of leverage, capital, and inventory intensity on tax avoidance. The present study was undertaken on the energy sector businesses listed on the Indonesia Stock Exchange (IDX) during the period spanning from 2016 to 2019. A purposive sampling strategy was employed to choose 22 companies, comprising a dataset of 88 observations. The data were subjected to analysis and hypothesis testing using the STATA software. A panel data estimation model determination test was conducted, which indicated that the standard effect model was appropriate for this research. The testing steps encompass many statistical procedures: the classical assumption test, panel data regression analysis, coefficient of determination test, and partial test. The study revealed a notable favorable impact of leverage and inventory intensity on CETR. In contrast, the effect of capital intensity on CETR was shown to be statistically insignificant. The results of this study support the positive accounting theory, which says that managers choose assessment methods and measure financial statement elements based on self-interest and opportunistic behavior. Specifically, management may opt for strategies that minimize tax liabilities or align with the company's goals, such as efficient contracting behavior, which aims to mitigate the risk of tax avoidance. Implications for Tax authorities in Indonesia should consider financial indicators, notably leverage, and inventory intensity, as valuable indicators of potential tax avoidance, particularly within the energy industry.